Analysis of the Effect of Warehousing Management System and Employee Ability on Work Productivity through Lean Warehousing in the Warehouses of the National Disaster Management Agency (BNPB) and the Regional Disaster Management Agency (BPBD) - Ghaddafi, Muhaiminul; Fatimah, Siti; Soekirman, Atong; Agusinta, Lira; Arubusman, Dian Artanti (Transpublika Publisher, 2025)
Indonesia is located along the equator and at the convergence of three major tectonic plates, making it prone to natural disasters such as earthquakes, tsunamis, and landslides. BNPB and BPBD manage disaster logistics using technology-based warehouse management systems (WMS) to improve aid distribution efficiency. This study examines the combined impact of warehouse management systems and employee capabilities on work productivity using a Lean Warehousing approach, which has not been extensively explored in previous research. The study was conducted at BNPB Jatiasih warehouse and BPBD warehouses across Java Island using observations, interviews, and questionnaires distributed to 98 respondents. Data were analyzed with SPSS 24.00, employing descriptive statistics, multiple regression, F-tests, t-tests, and the coefficient of determination (R²). Most respondents were male (76.8%) with a bachelor’s degree (39.8%). Validity tests showed that variables including inventory management, picking, item placement, employee skills, and lean warehousing had valid correlations above 0.202. Descriptive analysis indicated that warehouse management at BNPB and BPBD is effective but needs improvements in IT utilization, picking efficiency, inventory recording, and employee skills. Statistical tests confirmed that all variables significantly influence lean warehousing and productivity at a 95% confidence level. The study contributes novel insights by demonstrating how technology and employee capability synergistically enhance lean warehousing performance in disaster logistics. Strategic recommendations include routine employee training, strengthened cooperation through coaching and briefings, and optimized budget use via internal audits and independent utilization of logistical assets.